A longitudinal study of changes of congenital auricular deformity regarding self-correction. Issue 10 (October 2021) - Kim, Minsik; Lee, Hyun-Min; Choi, Sung-Won; Lee, Seokhwan; Kim, Choongrak; Kong, Soo-Keun; Lee, Il-Woo; Oh, Se-Joon
Summary: This study aimed to investigate the factors associated with congenital auricular deformities and evaluate the long-term frequency of their self-correction. Ninety newborns were enrolled in the study, and data were collected within 2 weeks after birth and at 1 year. The shape of the auricle was classified into seven categories using a digital image. At 2 weeks after birth, several birth-related factors were evaluated in the auricular deformity and normal groups. At 1 year after birth, the images of auricles were compared with the images at birth, and the changes in the auricle shape were investigated. Congenital auricular deformities were observed in 139 out of 180 ears, and the major type noted was helix rim deformity (47 ears), followed by normal ears (41 ears), and cup ears (33 ears). Male sex was found to have a statistically significant association with the occurrence of auricular deformity. In the longitudinal study, among 43 neonates (86 ears) followed-up 12 months later, the self-correction rate was approximately 50%. The normal auricle and prominent ear increased, helix rim deformity and cup ear decreased significantly. The prognosis of deformity varied depending on the type of deformity. Considering the low self-correction rate in the prominent and cup ears, newborns with these deformities might be recommended to undergo management such as auricle molding technique, as required.